Dictionary of archaeological terms : English-Spanish/Spanish-English = Vocabulario de conceptos arqueológicos : Inglés-Español/Español-Inglés - Salazar García, Domingo Carlos (Archaeopress, 2011)
This concise dictionary is intended to be helpful in the reading of archaeological books and publications from the Palaeolithic to the Middle Ages, and in the writing of papers and articles in both English and Spanish. The aim of this work is to help, in particular, students and on-site archaeologists to find quickly a word relating to a specific period, a specific area or a research field, in a book easy to carry everywhere. But this dictionary is also intended for everyone fond of archaeology, from prehistory to the Middle Ages.